"Die Soldaten der deutschen Wehrmacht helfen den sudetendeutschen Bauern bei der Einbringung der Ernte"
"Die Soldaten der deutschen Wehrmacht helfen den sudetendeutschen Bauern bei der Einbringung der Ernte".